Cu–Pd/γ-Al2O3 catalyzed the coupling of multi-step reactions: direct synthesis of benzimidazole derivatives. Issue 76 (1st August 2016) - Feng, Feng; Ye, Jia; Cheng, Zheng; Xu, Xiaoliang; Zhang, Qunfeng; Ma, Lei; Lu, Chunshan; Li, Xiaonian
Abstract : Catalyzed by the synergy effects of Cu–Pd bimetal and acidity of γ-Al2 O3, the transfer hydrogenation and successive cyclization coupling reaction from o -nitroaniline and alcohol to afford benzimidazole derivatives in high yield was realized. Abstract : The coupling of multi-step reactions catalyzed by a heterogeneous catalyst is an important path to accomplish some unconventional chemical transformations. Since the starting materials generated from previous steps were adsorbed on the catalyst, the activation energy of following steps was largely decreased, and thus the reaction conditions were more mild and environmental friendly. Catalyzed by a multifunctional Cu–Pd/γ-Al2 O3 catalyst, the transfer hydrogenation and successive cyclization coupling reaction from o -nitroaniline and alcohol to afford benzimidazole derivatives in high yield was realized. The catalyst could be reused several times without loss of activity. The synergies of reforming hydrogenation of Cu–Pd bimetal and support acidity of γ-Al2 O3 were responsible for this catalytic transformation.